2006
DOI: 10.4049/jimmunol.176.9.5161
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Inhibition of the Retinoid X Receptor (RXR) Blocks T Helper 2 Differentiation and Prevents Allergic Lung Inflammation

Abstract: Among the many factors regulating Th cell differentiation, some nuclear hormone receptors are emerging as important players. The retinoid X receptor (RXR) functions as heterodimerization partner for a variety of nuclear hormone receptors. We show in this study that RXR is critical for Th2-mediated immunity. An RXR antagonist inhibited Th2 differentiation, resulting in reduced production of IL-4, IL-10, and IL-13, whereas IFN-γ production was enhanced. This effect was dependent on the presence of APCs. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 19 publications
3
24
0
1
Order By: Relevance
“…The active metabolite of vitamin A, retinoic acid, acts to regulate gene transcription via two families of nuclear receptors, the retinoic acid receptor (RAR-␣, -␤, -␥) and the retinoid X receptor (RXR-␣, -␤, -␥) (8). In agreement with the data from dietary studies, disruption of the Rxr␣ gene can produce a Th1 bias (9,10) and treatment of mice with a retinoid X receptor antagonist can decrease Th2-mediated pulmonary eosinophilic inflammation (11).…”
supporting
confidence: 85%
“…The active metabolite of vitamin A, retinoic acid, acts to regulate gene transcription via two families of nuclear receptors, the retinoic acid receptor (RAR-␣, -␤, -␥) and the retinoid X receptor (RXR-␣, -␤, -␥) (8). In agreement with the data from dietary studies, disruption of the Rxr␣ gene can produce a Th1 bias (9,10) and treatment of mice with a retinoid X receptor antagonist can decrease Th2-mediated pulmonary eosinophilic inflammation (11).…”
supporting
confidence: 85%
“…Consistent with the reports of other groups, we found that Th2 cells preferentially express high levels of RXR␣. 31 However, we also found that Th17 cells were distinct in expressing high levels of RAR␣ and RAR␥. In addition, Th17 cells also express high levels of the orphan receptor ROR␥t, which was downregulated by ATRA ( Figure 3C).…”
mentioning
confidence: 61%
“…Acta Pharmacologica Sinica npg production in T cells [89] . Thus, the diverse anti-inflammatory effects of RXRα and its ligands in various cell types underscore their function in the prevention and treatment of inflammatory and metabolic disorders, such as cancer, atherosclerosis, insulin resistance, autoimmunity, and neurodegeneration.…”
Section: Wwwchinapharcom Zhang Xk Et Almentioning
confidence: 99%